PTU-023 Endoscopic ultrasound biopsy prior to palliative treatment for pancreatic cancer: can we prevent unnecessary procedures?. (8th June 2018) - Jalal, Mustafa; Wadsley, Jonathan; Hopper, Andrew
Abstract : Introduction: Pancreatic adenocarcinoma (PDAC) has a very poor prognosis with most patients presenting with advanced incurable disease. Palliative chemotherapy can have a significant improvement in survival, but given the potential severe complications patient assessment and histological confirmation with endoscopic ultrasound fine needle aspiration (EUS-FNA) is required. The rapid progression of PDAC can result in patients urgently travelling to tertiary centres and undergoing EUS-FNA (which is an invasive, sedated procedure with associated morbidity) prior to formal assessment in patients where the chemotherapy is subsequently not given. We aimed to see if there are pre-test prediction factors for non-uptake of palliative chemotherapy in PDAC in our cancer network. Methods: We retrospectively reviewed consecutive patients referred for EUS-FNA over a 2 year period for evaluation of inoperable locally advanced pancreatic masses on imaging. Details recorded were: age, body mass index (BMI), co-morbidity including cardiovascular, diabetes mellitus, chronic airway disease and anticoagulation. Also recorded were the World Health Organisation (WHO) performance status, position of the tumour and the requirement of a biliary stent. Patients who received chemotherapy were identified from the chemotherapy registry data. The diagnosis of PDAC was based on histological diagnosis or with clinical progression compatible with the diagnosis or death from malignancy. Results: In total 104 underwent EUS-FNA [55 men, mean age 68.5 years SD ±9.1]. All patients had a performance status of <3. Of these patients 50 (48.1%) went onto start palliative chemotherapy. None of the 8 patients≥80 years old who underwent EUS-FNA received chemotherapy compared to 50 out of 96 (52.1%) patients<80 years old ( p=0.0014). There were no other significant differences or predictors of chemotherapy uptake in patients when analysing presence of comorbidity, position of tumour, jaundice at presentation, WHO performance status and BMI <20. Conclusion: In this study, no patients over 80 years old having undergone EUS-FNA went on to receive palliative chemotherapy for PDAC. We would advise an initial oncology consultation first in these patients to avoid unnecessary EUS procedures. In patients under 80 years old clinical assessment should be considered when referring patients for suspected inoperable PDAC for EUS-guided FNA as only half go on to receive treatment, however no factors apart form age seemed to predict the uptake of palliative chemotherapy. Further validation of these outcomes could form a decision tool to decide who should be triaged to oncology clinics before EUS-FNA performed.